The acute and chronic effects of small-sided games training on specific aerobic condition of young soccer players - Stanganelli, L. C. R.; Pasquerelli, B. N.; Rabelo, F. N.; Matzenbacher, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The small-sided soccer games (SSG) have been indicated as an efficient method stimulate the aerobic energy system and its improvement has been reported to increase physical performance on match-play (Pasquarelli et al. 2010). The aim of the present study was to evaluate the acute and chronic effects of SSG training on aerobic conditioning of young soccer players. Methods: Twenty soccer players from Londrina City - Brazil participated in the study during the regular season (age:15.7± 0.5 years). Subjects were tested before and after the eight weeks of training for Running Economy (RE) in the laboratory and aerobic endurance in the field YoYo Intermittent Recovery Test Level 1(YYIR1). According to the YYIR1 results, the players were divided into two groups: higher (HG) or lower (LG) than the median YYIR1 performance score. This division was used during 14 SSG training sessions (any format) when the LG always trained with numerical inferiority. Results: At any format of SSG training, the average intensity was higher for the LG than for the HG (HRmax: 91.6- 89.5%; HRreserve: 87.8-85.5%; RPE: 5.6-4.9) at P<0.5. After eight weeks of training the LG group had a larger increase (14.6% ) than HG (4.6%) for YYIR1 maximal speed at P<0.01. The RE values decreased for 7 and 12 km/h but these adaptations were not statistically significant. The Hopkins´ model was applied to estimate the practical inferences based on magnitudes. For the YYIR1 test, it was inferred that the LG had 70% chance of a positive improvement when compared to the HG; 27% chance of this improvement being irrelevant when compared to the same group and 3% chance of this type of training promotes a negative effect in the performance of this field test. In both groups there was an increase of the magnitude of changes for RE. The chances of the percent changes being positive, irrelevant and negative were 25/70/4 percent for RE at 7km/h and 20/79/1 percent for RE at 12 km/h. Discussion: Based on these findings it could be inferred that training using the SSG is an efficient way of training young players. The summed effects of these loads significantly increased the specific aerobic conditioning of the subjects. Moreover, it was observed that LG, at first, may obtain magnitudes of change in aerobic conditioning more specifically, when including them in teams with numerical inferiority. Such changes were explained by higher intensities reached in the SSG (acute effects) and its subsequent effects summation (chronic adaptations).